IMPLEMENTASI KEBIJAKAN ACFTA (ASEAN-CHINA FREE TRADE AREA) DI KANTOR PELAYANAN UTAMA BEA DAN CUKAI TIPE A TANJUNG PRIOK - Pebriana Arimbhi; Yusuf Hutapea (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
The decision issued by the government indicates that the Indonesian government is ready to face ACFTA, but the facts say, Indonesia's domestic market is unable to compete with imported products from China that continue to flood the Indonesian domestic market. This study aims to find out how the implementation of the ACFTA policy in the Tanjung Priok Customs and Excise Service Office is related to the phenomenon of low export performance, push entities and any constraining entities that are simultaneously interconnected with the implementation of ACFTA policies. The research approach used is descriptive qualitative approach. From the result of the research, it is known that the implementation of ACFTA policy in KPUBC Type A Tanjung Priok still has not been implemented significantly, with the pushing entity that is disposition or attitude which includes government support, with the inhibiting entity that is not good communication yet unclear, inconsistency of information, human resources Few with poor competence, industrial competitiveness and low product quality, inadequate infrastructure, bureaucratic structure is still not good, fragmentation or organization is too broad.